Strategi Marketing Public Relations Brand Syariah Pada Industri Hotel: Studi Hotel Al Hanifi Banda Aceh - Yulian, Yasmine (Brand Communication, 2023)
This research suggests about the marketing public relations of Islamic hotels in Banda Aceh.) The marketing public relations activities of Islamic hotels are carried out with the aim of attracting consumers' interest with Islamic-based hotel services and facilities. As well as growing public awareness to use sharia hotels, this study uses a qualitative method with a descriptive approach. With data collection techniques through interviews, observation and documentation. From the results of this study, it can be concluded that marketing public relations in carrying out marketing strategies at the Al Hanifi hotel has several forms of strategies consisting of pull strategy (attracting), Push Strategy (pushing) and Pass Strategy (persuing) in marketing Public Relations activities. Data analysis was carried out using an interactive analysis model developed by Miles and Huberman covering the process of data collection, data reduction, data presentation and drawing conclusions. Based on the results of the study, it can be concluded that the marketing public relations of the Al Hanifi hotel has several strategies, such as maintaining guest trust, providing the best service, and sponsoring community events.